Utilization of waste wind turbine blades in performance improvement of asphalt mixture - Lan, Tianhui; Wang, Bingze; Zhang, Junchao; Wei, Hao; Liu, Xu (Frontiers in Materials, 2023)
Redundant wind turbine blades (WTB) retired from wind power facilities produce substantial waste annually and induce challenging environmental problems. As the mostly widely used materials for high-grade pavement construction, asphalt mixtures must have excellent high- and low-temperature performance, as well as water damage resistance, since pavement is subjected to complex loading, temperature, and humidity changes. This study proposed an asphalt mixture with the addition of two types of recycled WTB (rWTB), i.e., rWTB powders of granular sizes below 0.075 mm and rWTB fibers in the size range of 0.075 mm ~ 9.5 mm. Firstly, the thermogravimetric analysis results indicated the accepted thermal stability of rWTB material for the requirement of compaction, paving, and service condition of asphalt mixtures. Secondly, the properties of the asphalt mixtures modified by using (i) rWTB powder (5 wt%, 10 wt%, and 15 wt% in fine filler), (ii) rWTB fiber (0.1 wt%, 0.2 wt% and 0.3 wt% in fine aggregate), and (iii) both rWTB powder and fiber, were investigated by wheel tracking tests at 60oC, three-point bending tests at -10oC, and Marshall immersion tests. Experimental results showed that the rWTB asphalt mixtures could improve the overall road performance of asphalt mixtures, and that an optimal pavement performance could be obtained by the synergistic addition of rWTB powder and fiber. In addition, it was indicated that the improving mechanism of the rWTB material on asphalt mixture was mainly attributed to its good compatibility with asphalt binder, allowing the rWTB to strengthen asphalt mortar and improve the high- and low-temperature performance of asphalt mixture.